2017
DOI: 10.1111/area.12322
|View full text |Cite
|
Sign up to set email alerts
|

Making space for restoration: epistemological pluralism within mental health interventions in Kinshasa, Democratic Republic of Congo

Abstract: Global health policymakers have recently begun to focus their attention on high levels of untreated mental illness in low-and middle-income countries. They have, in turn, initiated a series of interventions intended to reduce the global 'treatment gap' that has emerged between those requiring treatment and those able to access it. Yet critics have challenged the questionable epistemological assumptions embedded in these interventions and have decried the lack of attention given to the translation and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For example, the potential to develop existing frameworks of formal care to accommodate alternative forms of healing, which are more prevalent in LMICs. 54 97 98 Alongside epistemological diversity, the framework emphasises the interdisciplinary nature of GMH and the capacity for potential linkage with other disciplines such as anthropology and geography. 52 54 ⁠ It is necessary that those working in the GMH field better acknowledge where their efforts specifically contribute along the continuum of engagement, therefore referencing the proposed framework may help encourage this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the potential to develop existing frameworks of formal care to accommodate alternative forms of healing, which are more prevalent in LMICs. 54 97 98 Alongside epistemological diversity, the framework emphasises the interdisciplinary nature of GMH and the capacity for potential linkage with other disciplines such as anthropology and geography. 52 54 ⁠ It is necessary that those working in the GMH field better acknowledge where their efforts specifically contribute along the continuum of engagement, therefore referencing the proposed framework may help encourage this.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a desire to see the cross-cultural adaptation of classifications and assessments of mental disorders, which are needed to facilitate research in culturally different contexts and allow for a global comparison. [50][51][52][53][54][55][56][57] GMH researchers demonstrate a more integrative, resourceful and pluralistic approach to solving mental health issues shared worldwide by seeking novel ideas and solutions to address them. 15 24 46 GMH is a highly interdisciplinary research area, benefiting from evidence generated from disciplines including epidemiology, geography and anthropology.…”
Section: Globalising Mental Health Researchmentioning
confidence: 99%
“…A population‐based study conducted in the eastern provinces identified that 40.5 percent of those surveyed met symptom criteria for major depressive disorder, 50.1 percent for PTSD, and 25.9 percent reported suicidal ideation over the previous 12 months (Johnson et al ., 2010). The national healthcare system is poorly equipped to respond to these complex and protracted emergencies with, for example, only 6 public mental health hospitals (with a combined 500 beds) in a country of 68 million people (Taylor, 2017). Access to essential medical supplies is irregular and rarely sufficient to meet complex needs (Taylor, 2020).…”
Section: Context Methods and Positionalitymentioning
confidence: 99%
“…An extensive literature considers the colonial origins of medicine and the many ways in which medicine and the colonial enterprise have interacted with one another (e.g., Arnold, ; Bashford, ; Lock & Nguyen, ; Redfield, ; Sheller, ). A growing literature on critical geographies of global health (e.g., Brown et al., ; Ingram, ; Taylor, ) urges us to “explore multiple temporalities and spatialities, including imperial and colonial historical geographies” (Brown et al., , p. 1183).…”
Section: Introductionmentioning
confidence: 99%